Investigação química e avaliação biológica de bauhinia pentandra (bong.) D.dietr. - Silva, Horlando Carlota da (2020)
The use of medicinal plants as a therapeutic resource is a popular knowledge that plays an important role in disease prevention and cure. Research has revealed that chemical constituents of plants of the genus Bauhinia exhibit various biological activities, such as acetylcholinesterase inhibitory, antibacterial, antibiotic modifier, cytotoxic, among others. However, there are still many species of this genus that need to be studied regarding the phytochemical profile. Thus, the present work reports the chemical and biological investigation of B. pentandra ethanolic stem extract (EEBPS), which resulted in the isolation and structural determination of eleven secondary metabolites: the mixture of steroids sitosterol and stigmasterol (BPC–1a and BPC–1b), two oxepin derivatives bauhiniastatin 1 (BPC–2) and bauhiniastatin 4 (BPC–3), seven 7,4'-dihydroxyflavan flavonoids (BPC–4), (2S)-liquiritigenin (BPC–5), (2S) - naringenin (BPC–6), isoliquiritigenin (BPC–7), poriol (BPC– 8), (-)-fisetinidol (BPC–9) and fisetin (BPC–10). It is noteworthy that BPC–8 is being described for the first time in the genus Bauhinia and with the exception of the steroid mixture, the other compounds are being reported for the first time in B. pentandra specie. The structures of the compounds were characterized by spectroscopic techniques such as IR, 1H and 13C NMR and retention times of standard HPLC samples, in addition to comparison with data described in the literature. Ethanolic extract (EEBPS), as well as isolated compounds BPC–2, BPC–3, BPC–4, BPC–5, BPC–6, BPC–7 and BPC–10 were evaluated as acetylcholinesterase inhibitors using the modified Ellman’s method. Among the evaluated substances, 7,4'-dihydroxyflavan (BPC–4) presented the best activity, with the inhibition halo diameter (0.9 cm) equal to that of eserine (reference standard). (-)-Fisetinidol (BPC–9) was evaluated for antibacterial activity and the modifying effect of antibiotic action on Staphylococcus aureus (SA1199-B and ATCC 25923), and Escherichia coli (ATCC 25922) strains, however, did not exhibit antibacterial activity against the bacteria tested, therefore presenting a minimum inhibitory concentration (MIC) value greater than 1024 µg/mL. It is noteworthy that in the combination of norfloxacin antibiotic with (-)-fisetinidol (BPC–9), it was possible to observe a reduction of its MIC value (1/4) 2 times to 32 µg/mL when compared with chlorpromazine (classic inhibitor), significance was observed, indicating that there was a reversal of bacterial resistance.